Virtual organisations: technologies, trends, standards and the contribution of the European R&D programs. (1st January 2003) - Filos, E.; Ouzounis, V. K.
Virtual organisations, or "organisations without walls", the collection of geographically distributed, functionally and culturally diverse organisational entities linked through information and communication technologies (ICTs), are key signposts of the shift from the industrial to the digital era. The article considers technologies and trends towards interoperable tools for organisational agility and flexibility based on distributed business operations. The European Commission has been supporting these developments through its various research programs since the early 1980s. Besides the notable research and technological development (R&D) achievements, important progress has also been made in the area of standardisation and through consensus building between the research and business communities in Europe. It is further recognised that technology alone will not be able to sustain the creative potential of the digital economy if the socio-economic, the legal and regulatory frameworks are not adequately taken into account. As more and more businesses are entering the digital economy, so the authors argue, more will be required than organisations merely becoming virtual they must become smart.